2019
DOI: 10.1038/s41467-019-08961-0
|View full text |Cite
|
Sign up to set email alerts
|

Organoid-derived C-Kit+/SSEA4− human retinal progenitor cells promote a protective retinal microenvironment during transplantation in rodents

Abstract: Stem cell therapy may replace lost photoreceptors and preserve residual photoreceptors during retinal degeneration (RD). Unfortunately, the degenerative microenvironment compromises the fate of grafted cells, demanding supplementary strategies for microenvironment regulation. Donor cells with both proper regeneration capability and intrinsic ability to improve microenvironment are highly desired. Here, we use cell surface markers (C-Kit+/SSEA4−) to effectively eliminate tumorigenic embryonic cells and enrich r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
106
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 101 publications
(112 citation statements)
references
References 62 publications
4
106
1
1
Order By: Relevance
“…The SCFR + donor cells survive up to 6 months in the subretinal space of host retina without generating teratoma. More importantly, in addition to robust material transfer and perfect cell replacement, these donor cells greatly inhibit the activation of microglia cells and improve the immune microenvironment of the RP disease (Chen et al, 2016;Zou et al, 2019). Our data well support the idea of SCFR + RPCs from a developmental view, and partially explain the advantages for transplantation, such as retinal multipotency, limited proliferation, strong survivability and proper migration.…”
Section: Discussionsupporting
confidence: 76%
“…The SCFR + donor cells survive up to 6 months in the subretinal space of host retina without generating teratoma. More importantly, in addition to robust material transfer and perfect cell replacement, these donor cells greatly inhibit the activation of microglia cells and improve the immune microenvironment of the RP disease (Chen et al, 2016;Zou et al, 2019). Our data well support the idea of SCFR + RPCs from a developmental view, and partially explain the advantages for transplantation, such as retinal multipotency, limited proliferation, strong survivability and proper migration.…”
Section: Discussionsupporting
confidence: 76%
“…In the current paper we have so far shown that it is KITL activation in photoreceptor cells themselves, rather than in RPE cells or potentially other retinal cells, that has protective effects on retinal degeneration, and that it is cell-autonomous KITL action that protects photoreceptor cells against degeneration. Nevertheless, other cell types also express KIT (Koso et al, 2007;Zou et al, 2019;Too et al, 2017 We have also shown that the pathway downstream of KIT involves a cytoplasm-to-nuclear shift of the transcription factor NRF2, which is likely mediated by KIT signaling-dependent activation of AKT (Yoo et al, 2017). Moreover, KIT signaling leads to increased expression of HMOX1 in an NRF2-dependent way.…”
Section: Aav-mediated Expression Of Neurotrophic Factors or Antioxidamentioning
confidence: 81%
“…Nevertheless, although KIT has been found to be expressed in retinal progenitor cells (Koso et al, 2007;Zou et al, 2019), its functional role in the adult retina is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Retinal ganglion cell (RGC) replacement provides a possible therapeutic strategy to reverse vision loss from optic neuropathies such as glaucoma, the world's leading cause of irreversible blindness. 1,2 Promising photoreceptor transplantation studies [3][4][5][6] (including human-rodent xenografts [7][8][9][10][11] ) provide proof of principle that vision restoration may be attainable by mammalian retinal cell replacement. However, unlike photoreceptors, RGCs are projection neurons and their functional replacement requires bidirectional visual pathway integration.…”
Section: Introductionmentioning
confidence: 99%